Mental, emotional and behavioural needs of the general population dollowing COVID-19 in India : findings from qualitative and quantitative studies - Parveen, Asma; Verma, Rajesh (Assistant professor of psychology) ([Place of publication not identified] : Routledge, 2025)
Mental, Emotional and Behavioural Needs of the General Population Following COVID-19 in India: Findings from Qualitative and Quantitative Studies explores the psychological challenges arising from COVID-19 that impacted the Indian general population. The book contains comprehensive research, conducted during and post-pandemic, on economic, social, psychological and health factors in the context of recovery, handling, coping and resilience. It also offers practical approaches for reproducing results and outcomes. These studies unmask several challenges, coping mechanisms and interventions adopted by the general population. The book covers a wide range of mental health domains, including offering insight into the impact of COVID-19 on the mental health status of those who have sustained the atrocities of cross-border terrorism and mass migration for more than three decades, and can still find meaning in life. The book navigates the complexities of risk factors and digital mental health interventions along with understanding the experiences of the general population through the lens of cultural narrative. It explores the social stigma, transitional impact and ruminative experiences of people who passed through the psychological grinding times and paves the way for effective interventions and resilience-building strategies in the post-pandemic era. It is a valuable reading for researchers, mental health practitioners, policymakers and educators to learn about the most recent developments, concerns, real-world difficulties encountered and solutions taken in the mental health field following COVID-19, as well as offering implementable methods for replication.
PrefaceChapter 1. Nature of Music Engagement and its Relation to Resilient Coping, Optimism and Fear of COVID-19Durgesh Kumar Upadhyay, Tushar Singh, Shalini Mittal and Bhawna TushirChapter 2. Adapting to Adversity: Understanding the Quality of Life Dynamics among Indian Adults Amidst and Beyond the COVID-19 PandemicAnurag Shukla, Gyanesh Kumar Tiwari, Archna Choudhary, Archana Singh and Amit Kumar MacoryaChapter 3. COVID-19 Outbreak and Mental Health: A Study from Jammuand KashmirSyed Inshaallah Tahir and Professor Tasleema JanChapter 4. Risk Factors and Emotional Health Consequences of Post-COVID-19 Syndrome in India: A Systematic ReviewNiti Upadhyay and Meenakshi ShuklaChapter 5. Post-COVID-19 India: Digital Mental Health Interventions for Disorder Prevalence PatternsUnnikannan P. Santhosh Kumar,Chetna Jaiswal and Nishi SrivastavaChapter 6. Cultural Narratives of Resilience: Exploring Mental Health Experiences of Rural India Post-COVID-19 Renisha JerineChapter 7. The Social Psychology of COVID-19 StigmaDivya Bhanot, Sunil Kumar Varma, Shivantika Sharad, Benkat Krishna Bharti, Tushar Singh, Shalini Mittal and Bhawna TushirChapter 8. Development and Validation of Middle School Underperformers Checklist in India Through Virtual Platforms Post-COVID-19Roseline Florence Gomes and Lijo ThomasChapter 9. Transitional Impact, Resilience Outcome Expectations, Mental Health, Resilience and Well-being During COVID-19 in IndiaJ. Hephsebha and Amrita DebChapter 10. Ruminative Reactive Patterns, Loneliness and Meaning in Life: Post-Second Wave of COVID-19Shubhangi Gupta,Shreya Chaudhary andRam Kumar GuptaChapter 11. Executive Summary: From the Editorś Pen [Keyboard]Rajesh Verma
Keywords: Quality of life; MEDICAL / Public Health; MEDICAL / Mental Health